Exploring the use of interactive technology in an intergenerational virtual campus - Bajaj Shreya (2014)
The development of interactive, participatory, multisensory environments that combine the physical with the virtual have arisen as a natural extension to the computer game industry’s constant race for more exciting user experiences.